Entre situações-limite e inéditos viáveis: problematizando as desigualdades de gênero nas aulas de educação física - Silva, Leandro de Carvalho da (2023)
This research has as its starting point the problem of gender exclusions observed in Physical Education classes, especially in opportunities where “self-managed” classes are held. In our teaching experiences, we found that although such exclusions are not common in classes in general, on occasions of free classes (self-organized), there is a greater exclusion of girls. Based on this problem, the objective of the present research was to analyze the limits and possibilities of a teaching intervention guided by a dialogical pedagogy with a view to problematizing gender inequalities in Physical Education classes. The study consisted in an action research, which addressed the thematic units Sports and Dances, structured in a didactic unit to address gender issues in a two-month period. The research universe comprised the students of the fifth year of elementary school, from a school in the municipal teaching network in the city of Suzano. The data production instruments consisted of class diaries, based on participant observations, video recordings and student narratives that emerged in the conversation circles, whose records were made through filming. Data analysis was performed using the Coding Categories method. The main results point to two major categories – Limit Situations and Viable Unpublished, and from these four subcategories emerge – Existential Fatigue, Antidialogicity, Dialogicity, Being More. We consider that the entire process, especially the moments of dialogue, action-reflection in the conversation circles, contributed to problematize Existential Tiredness and Antidialogicity, hoping through Dialogicity the possibility for students to overcome gender inequalities with a view to Being More.